(untitled) (Global Journal of Science Frontier Research, 2012)
Dimethyl sulphoxide –acetic anhydride reagent brings about an easy conversion of 1,3-indandione to its corresponding derivatives.At room.temperature this reagent converts 1,3- indandione to ylide(2),an unusual dimer(3) and a novel dimeric condensation product(6).However,at waterbath temperature it affords a spiran(8) along with (2) &(6).